Thromboendarterectomy without Circulatory Arrest for Chronic Pulmonary Thromboembolism : A Case Report - Kamiyoshihara, Mitsuhiro; Nameki, Taro; Takahashi, Toru; Ishikawa, Susumu; Ohtaki, Akio; Ohki, Shigeru; Morishita, Yasuo (Kita Kantō igaku (The Kitakanto Medical Journal), 2004)
A 44-year-old man with a chronic pulmonary thromboembolism underwent a pulmonary thromboendarterectomy without the method of deep hypothermia and circulatory arrest. A preliminary chest CT revealed thrombi in bilateral pulmonary arteries. Anticoagulant therapy was not effective, and the thrombi to the main pulmonary artery (PA) increased in size, thus emergent surgery was performed. Old thrombi were removed through a small transverse incision of the main PA under the support of extracorporeal circulation (ECC) with moderate hypothermia. Two types of curved vascular clamps were effective for removing the old thrombi : an atrial ear clamp into the right PA and an atrial clamp into the left PA. The aortic cross-clamp time was 43 minutes and the ECC time was 98 minutes. Our technique using a small incision in the PA and without circulatory arrest enables a minimally invasive strategy for the surgical treatment of chronic pulmonary thromboembolism.